A kind of hexanal sensor and preparation method thereof

By designing a YSZ solid electrolyte layer and a hexanal sensor for indium oxide and tin oxide composite sensitive electrodes, the problem of difficult to quickly detect hexanal in respiratory gases in the prior art is solved, and a high selectivity and sensitivity detection effect is achieved, which is suitable for early diagnosis of lung cancer.

CN115753938BActive Publication Date: 2025-04-08SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211340976.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-30
Publication Date
2025-04-08
Estimated Expiration
2042-10-30

AI Technical Summary

Technical Problem

The prior art is difficult to detect hexanal in respiratory gases quickly, conveniently and non-destructively, resulting in difficulty in early diagnosis of lung cancer.

Method used

A hexanal sensor including a YSZ solid electrolyte layer, a heating sheet, a reference electrode and a sensitive electrode was designed. The sensitive electrode material is a composite of indium oxide and tin oxide. The microstructure of the sensitive electrode is optimized through different sintering temperatures to improve the selectivity and sensitivity to hexanal.

Benefits of technology

It realizes high selective detection of hexanaldehyde, the sensor is simple in structure, convenient in operation, cheap and portable, and is suitable for rapid clinical testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115753938B_ABST
    Figure CN115753938B_ABST
Patent Text Reader

Abstract

The present invention relates to a hexanal sensor and a preparation method thereof. The sensor comprises a YSZ solid electrolyte layer (1), a heating plate (2), a reference electrode (3) and a sensitive electrode (4). The lower surface of the YSZ solid electrolyte layer (1) is attached to the heating plate (2), and the upper surface is provided with a reference electrode (3) and a sensitive electrode (4) at intervals. The material of the sensitive electrode (4) is a composite of indium oxide and tin oxide. Compared with the prior art, the present invention can achieve highly selective detection of hexanal in mixed gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical sensors, and in particular to a hexanal sensor and a preparation method thereof. Background Art

[0002] Lung cancer refers to a malignant epithelial tumor, which originates from bronchial epithelium, bronchial mucous glands, bronchiolar epithelium and alveolar epithelium, etc., called bronchial lung cancer, or lung cancer for short. At present, the incidence and mortality of lung cancer have ranked first among various malignant tumors. The incidence and mortality of cancer in my country have been on the rise, and about 600,000 people die of lung cancer every year. Clinically, the common diagnostic methods for lung cancer are as follows: X-ray examination, computerized tomography, magnetic resonance tomography, sputum exfoliated cell examination, fiberoptic bronchoscopy, and percutaneous lung puncture biopsy. The above conventional lung diagnosis methods are complicated, time-consuming and expensive, and can also cause damage to patients, so they are not conducive to large-scale census, thereby delaying the best treatment time. If lung cancer is diagnosed and treated in the early stage, the survival rate of lung cancer patients can rise to 88% after five years. Therefore, developing a convenient, fast and non-destructive auxiliary diagnosis method for lung cancer has great practical and social significance. The growth of tumors is often accompanied by changes in genes or proteins, which can lead to oxidation of cell membranes, and tumor cells then release volatile organic compounds (VOCs). Cellular metabolites enter the circulatory system through the microenvironment in which they live, and most of them are excreted from the body through the gas exchange of the lungs. By detecting the composition and content of volatile and semi-volatile organic compounds in human respiratory gas, the disease can be diagnosed, that is, respiratory diagnosis. Michael Phillips determined that lung cancer patients have 22 types of VOCs volatile organic gases, among which at least hexanal is included. The current method for respiratory diagnosis of hexanal is solid phase microextraction-assisted gas chromatography-mass spectrometry technology. Due to the high cost and cumbersome and time-consuming detection process, it is very difficult to apply it to clinical rapid detection. Therefore, designing a sensor with high selectivity for the detection of hexanal is of great practical significance for the realization of respiratory diagnosis of lung cancer patients. How to build a cheap portable sensor with high selectivity for the detection of hexanal has become an urgent problem to be solved. Summary of the invention

[0003] The purpose of the present invention is to provide a hexanal sensor and a preparation method thereof.

[0004] The purpose of the present invention can be achieved by the following technical scheme: a hexanal sensor, characterized in that it includes a YSZ solid electrolyte layer, a heating plate, a reference electrode and a sensitive electrode, the lower surface of the YSZ solid electrolyte layer is attached to the heating plate, and the reference electrode and the sensitive electrode are arranged on the upper surface at intervals, and the material of the sensitive electrode is a composite of indium oxide and tin oxide.

[0005] Preferably, in the composite, the mass ratio of indium oxide to tin oxide is 7:(2-4).

[0006] Further preferably, in the composite, the mass ratio of indium oxide to tin oxide is 7:3.

[0007] Preferably, a reference electrode and a sensitive electrode are disposed on the YSZ solid electrolyte layer at intervals.

[0008] Preferably, the material of the heating plate is aluminum oxide, and the material of the reference electrode is manganese dioxide.

[0009] Preferably, the YSZ solid electrolyte layer and the heating plate are both in the shape of a cuboid, and the length and width of the YSZ solid electrolyte layer are equal to those of the heating plate. The reference electrode and the sensitive electrode are respectively in the shape of a cuboid of the same size. A reference electrode lead is provided on the reference electrode, and a sensitive electrode lead is provided on the sensitive electrode.

[0010] Further preferably, the length of the YSZ solid electrolyte layer and the heating plate ranges from 1.3 cm to 1.7 cm, the width ranges from 2 cm to 3 cm, the thickness of the YSZ solid electrolyte layer ranges from 0.5 cm to 1 cm, and the thickness of the heating plate ranges from 1.1 mm to 1.5 mm.

[0011] Further preferably, the reference electrode and the sensitive electrode have a length ranging from 4 mm to 6 mm, a width ranging from 4 mm to 6 mm, and a thickness ranging from 14 um to 16 um.

[0012] A method for preparing the above-mentioned hexanal sensor comprises the following steps:

[0013] S1: Print a slurry containing manganese dioxide on the upper end surface of the YSZ solid electrolyte layer by screen printing, and sinter it after drying to form a reference electrode;

[0014] S2: Printing a slurry containing indium oxide and tin oxide on the upper end surface of the YSZ solid electrolyte layer by screen printing and drying to form a sensitive electrode;

[0015] S3: applying Pt paste on the surfaces of the reference electrode and the sensitive electrode respectively, and then leading out the reference electrode lead and the sensitive electrode lead respectively through the Pt paste, and sintering them after drying;

[0016] S4: Place the heating plate under the YSZ solid electrolyte layer, and stick the heating plate and the YSZ solid electrolyte layer together using a high temperature resistant adhesive, and the sensor is prepared.

[0017] Preferably, in the sintering process described in step S3, the sintering temperature is 900-1100°C.

[0018] Further preferably, in the sintering process described in step S3, the sintering temperature is 950-1050°C.

[0019] Preferably, in the sintering process described in step S3, the sintering temperature is 1000°C.

[0020] Preferably, the preparation method of the slurry containing manganese dioxide in step S1 is: putting manganese dioxide powder and pinene alcohol slurry into an agate mortar, mixing and grinding them evenly to obtain the slurry containing manganese dioxide, wherein the pinene alcohol slurry is prepared by mixing pinene alcohol and ethyl cellulose.

[0021] Preferably, the preparation method of the slurry containing indium oxide and tin oxide described in step S2 is: indium oxide and tin oxide are put into an agate mortar and mixed with pinene alcohol slurry and ground evenly to obtain a slurry containing indium oxide and tin oxide, wherein the pinene alcohol slurry is prepared by mixing pinene alcohol and ethyl cellulose.

[0022] At present, gas sensors based on yttria stabilized zirconia (YSZ or zirconium-based) electrolytes have attracted wide attention due to their applicability to extreme environments (high temperature and high humidity) and their relatively high selectivity and low cost. Among them, zirconium-based gas sensors equipped with oxide sensitive electrodes are the most widely studied. However, there are currently no reports on the highly selective detection of hexanal by such zirconium-based sensors. The present invention proposes for the first time a zirconium-based sensor that has a highly selective response to hexanal.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] 1. The present invention provides a portable electrochemical sensor and a preparation method thereof, which can realize highly selective detection of hexanal in mixed gas;

[0025] 2. The present invention only requires one sensitive electrode, without optical coupling and complex algorithms, to achieve high selectivity for hexanal gas;

[0026] 3. The present invention uses stabilized zirconium oxide (YSZ) as an ion conductive layer, uses indium oxide and tin oxide composite oxide materials with high electrochemical catalytic activity as sensitive electrodes, and changes the micromorphology of the sensitive electrode layer by different sintering temperatures (950°C to 1050°C), thereby obtaining a sensitive electrode layer with different pore structures, optimizing the microstructure of the sensitive electrode, and facilitating the gas to be measured to quickly reach the three-phase interface to participate in the electrochemical reaction, thereby improving the high selectivity and sensitivity of the sensor to hexanal gas;

[0027] 4. The sensor of the present invention has a simple structure, is easy to operate, and is cheap and portable. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a structural schematic diagram of the sensor of the present invention;

[0029] Figure 2 The response curve of the sensitive electrode of the sensor when the sensor of the present invention is used to test the mixed gas of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone;

[0030] Figure 3 In order to use the sensor of the present invention to test the hexanal mixed gas, when the concentration of the mixed gas changes from 0 to 5 ppm, the response step curve of the sensitive electrode of the sensor;

[0031] Figure 4 When the sensor of the present invention is used to test a mixed gas of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone, the response step curve of the sensitive electrode of the sensor when the composite ratio of indium oxide and tin oxide material changes from 0% to 60%;

[0032] Figure 5 To test the optimal sintering temperature of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone mixed gas using the sensor of the present invention, the sensor outputs a response curve when the sintering temperature of the sensor changes from 950°C to 1050°C;

[0033] Figure 6 A comparison chart of the response curves of the sensor of the present invention for testing a mixed gas of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone, and for testing a mixed gas of unmixed materials as sensitive electrodes of the sensor;

[0034] Figure 7 The sensor of the present invention is used to perform anti-interference test on hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone gases under the optimal composite ratio, optimal sintering temperature and test temperature, and the sensor outputs a response curve;

[0035] In the figure: 1-YSZ solid electrolyte layer, 2-heating plate, 3-reference electrode, 4-sensitive electrode. DETAILED DESCRIPTION

[0036] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.

[0037] Example 1

[0038] like Figure 1As shown, a hexanal sensor comprises a YSZ solid electrolyte layer 1, a heating plate 2, a reference electrode 3 and a sensitive electrode 4, the YSZ solid electrolyte layer 1 and the heating plate 2 are both in the shape of a cube, and the side length of the YSZ solid electrolyte layer 1 is equal to the side length of the heating plate 2, the lower end surface of the YSZ solid electrolyte layer 1 is fitted with and fixedly connected to the upper end surface of the heating plate 2, the reference electrode 3 and the sensitive electrode 4 are respectively in the shape of a cube with the same size, the reference electrode 3 and the sensitive electrode 4 are spaced and distributed on the upper end surface of the YSZ solid electrolyte layer 1, the lower end surface of the reference electrode 3 and the lower end surface of the sensitive electrode 4 are respectively fitted with and fixedly connected to the upper end surface of the YSZ solid electrolyte layer 1, the material of the sensitive electrode 4 is indium oxide composited with 30% tin oxide (that is, the weight of the tin oxide is 30% of the total weight of indium oxide and tin oxide), and the material of the reference electrode 3 is manganese dioxide; a reference electrode lead is provided on the reference electrode 3, and a sensitive electrode lead is provided on the sensitive electrode 4; the preparation method specifically comprises the following steps:

[0039] (1) preparing a YSZ solid electrolyte layer 1 and a heating plate 2 of corresponding sizes according to design size requirements;

[0040] (2) mixing terpineol and ethyl cellulose in a mass ratio of 94:6 to prepare terpineol slurry;

[0041] (3) mixing manganese dioxide powder and pinene alcohol slurry in a mass ratio of 1:1.5 in an agate mortar and grinding them evenly to form a first slurry;

[0042] (4) using screen printing technology to print the first slurry at the design position of the reference electrode 3 on the upper end surface of the YSZ solid electrolyte layer 1 according to the design size to obtain a prototype of the reference electrode 3;

[0043] (5) placing the product obtained in step (4) in a drying oven, drying at 130° C. for 12 hours, and then placing it in a sintering furnace, sintering at 1400° C. for 2 hours, and then cooling to room temperature to form a reference electrode 3 on the upper end surface of the YSZ solid electrolyte layer 1;

[0044] (6) Indium oxide and tin oxide in a mass ratio of 7:3 and terpineol slurry in a mass ratio of 1:1.5 were placed in an agate mortar, mixed and ground evenly to form a second slurry;

[0045] (7) Printing the second slurry at the designed position of the sensitive electrode 4 on the upper end surface of the YSZ solid electrolyte layer 1 according to the designed size by screen printing technology to obtain a prototype of the sensitive electrode 4;

[0046] (8) The product obtained after the treatment in step (7) is placed in a drying oven, the temperature of which is set to 130° C., and dried for half an hour. The product is taken out and cooled to room temperature, and a sensitive electrode 4 is formed on the upper end surface of the YSZ solid electrolyte layer 1;

[0047] (9) Pt paste is applied on the surfaces of the reference electrode 3 and the sensitive electrode 4, respectively, and then the reference electrode lead and the sensitive electrode lead are respectively led out through the Pt paste;

[0048] (10) placing the product obtained after the treatment in step (9) in a drying oven at 130° C. for 12 hours, then taking it out and placing it in a sintering furnace at 900° C. for 2 hours to form it, and then taking it out and cooling it to room temperature;

[0049] (11) The heating plate 2 is placed below the YSZ solid electrolyte layer 1 in the product obtained after the treatment in step (10), and the heating plate 2 and the YSZ solid electrolyte layer 1 are adhered together with a high temperature resistant adhesive. The sensor is thus prepared.

[0050] Example 2

[0051] A hexanal sensor, wherein the material of the heating plate 2 is aluminum oxide, the length of the YSZ solid electrolyte layer 1 is lcm, the width of the YSZ solid electrolyte layer 1 is dcm, the thickness of the YSZ solid electrolyte layer 1 is hmm, the length of the heating plate 2 is lcm, the width of the heating plate 2 is d1cm, the thickness of the heating plate 2 is h1mm, wherein the value range of l is 1.3cm-1.7cm, the value range of d is 2cm-3cm, the value range of h is 0.5cm-1cm, the value range of h1 is 1.1mm-1.5mm, the length of the reference electrode 3 and the sensitive electrode 4 are l1 respectively, the width of the reference electrode 3 and the sensitive electrode 4 is d1, the thickness of the reference electrode 3 and the sensitive electrode 4 is h2, wherein the value range of l1 is 4mm-6mm, the value range of d1 is 4mm-6mm, and the value range of h2 is 14um-16um. The rest is the same as that of Example 1.

[0052] After the sensor is prepared, its performance is evaluated by building a complete test platform, and at the same time, it provides a basis for actual production applications. The sample gas is introduced into the test device by dynamically preparing the gas. In the sensor test device, the quartz tube is a flow device for gas in and out, which is placed on an iron frame. The operating temperature of the sensor is controlled by a 220V DC regulated power supply, a heating plate, and a thermocouple. The sensor is placed in the quartz tube by fitting it with the ceramic tube and the heating plate. Platinum wire needs to be inserted into the pores of the ceramic tube to ensure that the sensor signal can be connected to the external acquisition signal source. A wooden plug needs to be inserted into the ceramic tube. After the quartz tube is connected, the gap between the ceramic tube and the quartz tube is filled with a wooden plug to ensure that the test gas is in a closed space. The test process is roughly divided into the following steps:

[0053] 1) Place the prepared gas sensor in a quartz tube, seal the test chamber, and perform an airtightness check on the test chamber.

[0054] 2) Adjust the DC regulated power supply to provide a certain voltage to the heater so that the sensor can work stably within a certain operating temperature range.

[0055] 3) A certain amount of background gas is introduced into the test chamber, and the Agilent 34970A collects signals in real time. When the time-voltage curve becomes stable, the sensor is judged to have entered a quasi-steady state, and the target test gas is introduced. When the introduced target gas makes the sensor signal stable and no longer changes significantly, the test chamber is replaced with background gas, and the sensor is ready for the next measurement when it enters a stable state again.

[0056] Figure 2 (a) The electrochemical sensor of the present invention is used to test a mixed gas of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone, and the response curve of the sensitive electrode of the electrochemical sensor of the present invention is shown when the concentration of the mixed gas is 1 ppm and the operating voltage is 9 V; Figure 2 (b) The electrochemical sensor of the present invention is used to test a mixed gas of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone, and the response step curve of the sensitive electrode of the electrochemical sensor of the present invention when the concentration of the mixed gas is 1 ppm and the operating voltage is 10 V; Figure 2 (c) The electrochemical sensor of the present invention is used to test a mixed gas of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone. When the concentration of the mixed gas is 1 ppm and the operating voltage is 11 V, the response step curve of the sensitive electrode of the electrochemical sensor of the present invention is obtained;

[0057] The electrochemical sensor of the present invention is used to test a mixed gas of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone. When the concentration of the mixed gas is 1 ppm and the operating voltage is 9 to 11 V, the response step curve of the sensitive electrode of the electrochemical sensor of the present invention is as follows: Figure 2 (a)(b)(c); when the electrochemical sensor of the present invention is used to test the hexanal mixed gas, when the concentration of the mixed gas changes from 0 to 5 ppm, the response step curve of the sensitive electrode of the electrochemical sensor of the present invention is shown in FIG (3); when the electrochemical sensor of the present invention is used to test the hexanal, n-hexane, styrene, ethylbenzene, isoprene, acetone mixed gas, when the composite ratio of indium oxide and tin oxide material changes from 0% to 60%, the response step curve of the sensitive electrode of the electrochemical sensor of the present invention is shown in FIG. Figure 4As shown; the electrochemical sensor of the present invention is used to test the optimal sintering temperature of hexanal, n-hexane, styrene, ethylbenzene, isoprene, and acetone mixed gas. After the sensitive material is evenly printed on the surface of the YSZ solid electrolyte, when the sensor sintering temperature changes from 950°C to 1050°C, the output response curve of the electrochemical sensor of the present invention is as shown Figure 5 The sensor of the present invention is used to test the mixed gas of hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone, and the response curve comparison of the single sensitive material as the sensitive electrode of the sensor is shown in the figure below. Figure 6 The sensor of the present invention is used to perform anti-interference tests on hexanal, n-hexane, styrene, ethylbenzene, isoprene and acetone gases at the optimal composite ratio, optimal sintering temperature and test temperature. The sensor output response curve is shown in FIG. Figure 7 shown.

[0058] analyze Figure 2 (a)(b)(c) It can be seen that the hexanal electrochemical sensor exhibits the best selectivity for hexanal when the operating voltage is 10V. Figure 3 It can be seen that the hexanal electrochemical sensor shows good selectivity for 0.8ppm to 5ppm of hexanal, and reaches sensor saturation when the concentration is about 3ppm. Figure 4 It can be seen that in the sensitive electrode of the hexanal electrochemical sensor, when the composite ratio of indium oxide to tin oxide is 7:3, the sensor exhibits the best selectivity for hexanal gas and the electrochemical sensor of the present invention exhibits high sensitivity to hexanal. Figure 5 It can be seen that the sensor of the present invention achieves high selectivity and sensitivity to hexanal gas when the sensor sintering temperature is 1000°C. Figure 6 It can be seen that when a single material is used as the sensor sensitive electrode, the sensor has no high selectivity and sensitivity to hexanal gas. However, when a certain proportion of composite materials is used as the sensor sensitive electrode, the sensor has good selectivity and sensitivity to hexanal gas. Figure 7 It can be seen that when the sensor is introduced into a mixed high-concentration interfering gas, the sensor can still maintain its single selectivity to hexanal gas and is not affected by other gases.

[0059] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A hexanal sensor, characterized in that It comprises a YSZ solid electrolyte layer (1), a heating plate (2), a reference electrode (3) and a sensitive electrode (4); the lower surface of the YSZ solid electrolyte layer (1) is attached to the heating plate (2); the upper surface is provided with a reference electrode (3) and a sensitive electrode (4) at intervals; the material of the sensitive electrode (4) is a composite of indium oxide and tin oxide; The mass ratio of indium oxide to tin oxide is 7:3; The preparation method of the hexanal sensor comprises the following steps: S1: printing a slurry containing manganese dioxide on the upper end surface of the YSZ solid electrolyte layer (1) by screen printing, and sintering it after drying to form a reference electrode (3); S2: printing a slurry containing indium oxide and tin oxide on the upper end surface of the YSZ solid electrolyte layer (1) by screen printing, and drying to form a sensitive electrode (4); S3: applying Pt paste on the surfaces of the reference electrode (3) and the sensitive electrode (4), respectively, and then leading out the reference electrode lead and the sensitive electrode lead through the Pt paste, respectively, and sintering them after drying; S4: placing the heating sheet (2) below the YSZ solid electrolyte layer (1), and bonding the heating sheet (2) and the YSZ solid electrolyte layer (1) together using a high temperature resistant adhesive, and the sensor is prepared; The preparation method of the slurry containing indium oxide and tin oxide described in step S2 is: indium oxide and tin oxide are put into an agate mortar and mixed with pinene alcohol slurry and ground evenly to obtain a slurry containing indium oxide and tin oxide, wherein the pinene alcohol slurry is prepared by mixing pinene alcohol and ethyl cellulose; In the sintering process described in step S3, the sintering temperature is 1000°C.

2. The hexanal sensor according to claim 1, characterized in that: A reference electrode (3) and a sensitive electrode (4) are arranged on the YSZ solid electrolyte layer (1) at intervals.

3. The hexanal sensor according to claim 1, characterized in that: The material of the heating plate (2) is aluminum oxide, and the material of the reference electrode (3) is manganese dioxide.

4. The hexanal sensor according to claim 1, characterized in that: The YSZ solid electrolyte layer (1) and the heating plate (2) are both in the shape of a rectangular parallelepiped, and the length and width of the YSZ solid electrolyte layer (1) are equal to the length and width of the heating plate (2). The reference electrode (3) and the sensitive electrode (4) are both in the shape of a rectangular parallelepiped with the same size. A reference electrode lead is provided on the reference electrode (3), and a sensitive electrode lead is provided on the sensitive electrode (4).

5. The hexanal sensor according to claim 4, characterized in that: The length of the YSZ solid electrolyte layer (1) and the heating plate (2) ranges from 1.3 cm to 1.7 cm, and the width ranges from 2 cm to 3 cm. The thickness of the YSZ solid electrolyte layer (1) ranges from 0.5 cm to 1 cm, and the thickness of the heating plate (2) ranges from 1.1 mm to 1.5 mm.

6. The hexanal sensor according to claim 4, characterized in that: The reference electrode (3) and the sensitive electrode (4) have a length ranging from 4 mm to 6 mm, a width ranging from 4 mm to 6 mm, and a thickness ranging from 14 μm to 16 μm.

7. The hexanal sensor according to claim 1, characterized in that: The preparation method of the slurry containing manganese dioxide described in step S1 is: put manganese dioxide powder and pinene alcohol slurry into an agate mortar, mix and grind them evenly to obtain the slurry containing manganese dioxide, wherein the pinene alcohol slurry is prepared by mixing pinene alcohol and ethyl cellulose.